Comparison of the Contributions of Heat-Labile Enterotoxin and Heat-Stable Enterotoxin b to the Virulence of Enterotoxigenic Escherichia coli in F4ac Receptor-Positive Young Pigs - Erume, Joseph (American Society for Microbiology (ASM), 2008)
In swine, the most common and severe enterotoxigenic Escherichia coli (ETEC) infections are caused by strains that express K88 (F4)(+) fimbriae, heat-labile enterotoxin (LT), heat-stable enterotoxin b (STb), and enteroaggregative E. coli heat-stable toxin 1. Previous studies based on a design that involved enterotoxin genes cloned into a nontoxigenic fimbriated strain have suggested that LT but not STb plays an important role in dehydrating diarrheal disease in piglets <1 week old and also enhances bacterial colonization of the intestine. In the present study, we compared these two toxins in terms of importance for piglets >1 week old with a study design that involved construction of isogenic single- and double-deletion mutants and inoculation of 9-day-old F4ac receptor-positive gnotobiotic piglets. Based on the postinoculation percent weight change per h and serum bicarbonate concentrations, the virulence of the STb(−) mutant (ΔestB) did not significantly differ from that of the parent. However, deletion of the LT genes (ΔeltAB) in the STb(−) mutant resulted in a complete abrogation of weight loss, dehydration, and metabolic acidosis in inoculated pigs, and LT complementation restored the virulence of this strain. These results support the hypothesis that LT is a more significant contributor than STb to the virulence of F4(+) ETEC infections in young F4ac receptor-positive pigs less than 2 weeks old. However, in contrast to previous studies with gnotobiotic piglets, there was no evidence that the expression of LT enhanced the ability of the F4(+) ETEC strain to colonize the small intestine.